Vitamin D Insufficiency Among the Adult Women of Remote Areas of Pakistan. - Niaz Hussain Keerio1, Nasrullah Aamer2, Raheel Akbar Baloch3, ,Nouman Memon4, Arslan Abro5 , Syed Shahid Noor6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2020)
Objectives: Vitamin D efficiency is widely prevalent even in tropical countries like Pakistan, where there is plentiful sunshine. Vitamin D deficiency is more common in middle age and elderly females. Methods: Our study was a community-based cross-sectional study that was conducted from December 2018 to March 2019. This study was conducted in multiple villages in the remote area of Hyderabad district of Pakistan. In this study, we included 388 women age above 40 years. Multistage random sampling was used for this study. Each participant was interviewed and recorded on organized proforma. SPSS version 25 was used for data entry and analysis. Participants with laboratory repot of having less than 30ng/ml 25OH vitamin D were said to have vitamin D insufficiency (VDI). Results: ln our study out of 388 contributors, 70.6% of participants had Vitamin D Insufficiency (VDI) ( 51 0%). The mean (SD) age of the participant was 54 years. Mean (SD) sun exposure was 120(59.2) minutes. 148 (38.1%) were obese. Only 146 (37.6o/o) were on satisfactory diet. Test results revealed decreasing sun light exposure, over weight and inadequate diet as significant factors of Vitamin D insufficiency. Conclusion: In our study we identified important causes associated with VDI in remote areas of Pakistan. We propose all females of age above 40 years should take diet rich in Vitamin D, adequate sun exposure and regularly taking vitamin D supplements and maintain body weight to help to control the VDI significantly.